Expression of IL‐33 and its receptor ST2 in chronic rhinosinusitis with nasal polyps. (19th November 2013) - Baba, Shintaro; Kondo, Kenji; Kanaya, Kaori; Suzukawa, Keigo; Ushio, Munetaka; Urata, Shinji; Asakage, Takahiro; Kakigi, Akinobu; Suzukawa, Maho; Ohta, Ken; Yamasoba, Tatsuya
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Interleukin (IL)−33 is a novel member of the IL‐1 cytokine family and a ligand for the orphan IL‐1 family receptor ST2. IL‐33 induces T helper 2‐type inflammatory responses and is considered to play a crucial role in allergic inflammatory reactions such as asthma and atopic dermatitis. However, the role of IL‐33 and its receptor ST2 in chronic rhinosinusitis remains unclear. Study Design In vitro study. Methods The expression patterns of IL‐33 and ST2 at both mRNA and protein levels in nasal polyps from eosinophilic chronic rhinosinusitis (ECRS) patients (n = 10) and non‐ECRS patients (n = 13), as well as in seemingly normal mucosa of the uncinate processes in patients without sinusitis (control; n = 5), were compared using immunohistochemical staining, enzyme‐linked immunosorbent assay, and real‐time polymerase chain reactions. Results ST2‐positive cells in the inflammatory cells in the subepithelial layer were significantly higher in the ECRS group than other groups. The expression of ST2 mRNA in polyps of the ECRS group was significantly increased compared with controls. Many ST2‐positive eosinophils were observed in the mucosa of ECRS but not in the mucosa of non‐ECRS patients. The expression level of IL‐33 mRNA was not significantly different among the three groups. Conclusions The current study suggests that IL‐33 and its receptor ST2 may play important roles in the pathogenesis of chronic rhinosinusitis, especially in ECRS, through the increased expression of ST2 in eosinophils. Level of Evidence N/A. Laryngoscope, 124:E115–E122, 2014